The Discourse of Medical Malpractice Punishment In Criminology Perspective - Lalu M. Guntur Payasan W.P. (SOEPRA, 2020)
Abstract: Medical malpractice is a phenomenon that familiar case in Indonesia. However, the variety is based on intensity and attention that is missed in the academic study. The trends of medical malpractice also fluctuate, both through the Konsil Kedokteran (KKI) to the process at Majelis Kehormatan Dewan Kedokteran Indonesia (MKDKI). Firstly, the case was identified in 1923 until now with more ways, including negligence in drug receipt, abortion, surgery to anesthesia. This paper examines the implementation of medical malpractice punishment in criminological perspectives. There are 3 (three) issues, such as the perspective of medical malpractice as a crime, the neutralization of malpractice as a part of medical practice, and the proficiency gap in the judicial process. Medical malpractice punishments in constitutive penology studies are rooted in the provision of health services, the ratio of medical expertise, the effectiveness discourse of imprisonment, and non-capital punishment. The conclusion is so necessary to reconstruct discourse about the punishment of malpractice by focusing on the process of social reintegration. This can be done in the form of social work responsibilities.Keywords: criminology, medical malpractice, punishment Abstrak: Malapraktik medis merupakan fenomena yang kerap terjadi di Indonesia. Namun, dengan intensitas dan perhatian yang seringkali luput dalam kajian. Tren malapraktik medis di Indonesia pun mengalami fluktuasi, baik melalui Konsil Kedokteran Indonesia (KKI) hingga proses di Majelis Kehormatan Dewan Kedokteran Indonesia (MKDKI). Salah satu kasus yang teridentifikasi sebagai malapraktik medis telah terjadi sejak 1923 hingga kini dengan ragam modus, meliputi kelalaian dalam pemberian obat, aborsi, bedah, hingga anestesi. Tulisan ini mengkaji implementasi penghukuman malapraktik medis dalam perspektif kriminologi. Hal ini dilakukan mengingat fenomena serupa seringkali hanya dilihat dari sudut pandang hukum. Terdapat 3 (tiga) isu yang diketengahkan, yakni perspesi malapraktik medis sebagai kejahatan, netralitas malapraktik medis sebagai bagian dari praktik kedokteran, dan celah kecapakan dalam proses peradilan. Penghukuman malapraktik medis dalam kajian penologi konstitutif berakar pada penyediaan layanan kesehatan, rasio kepakaran tenaga medis, diskursus efektifitas pemenjaraan, dan hukuman non kapital. Simpulannya bahwa perlu rekonstruksi pemikiran tentang penghukuman malapraktik dengan menitikberatkan pada proses reintegrasi sosial. Hal ini dapat dilakukan dalam bentuk tanggung jawab kerja sosial.Kata kunci: kriminologi, malapraktik medis, penghukuman